Bioequivalence of a new coated 15 mg primaquine formulation for malaria elimination - Nguyen Ngoc Pouplin, J; Kaendiao, T; Rahimi, BA; Soni, M; Basopia, H; Shah, D; Patil, J; Dholakia, V; Suthar, Y; Tarning, J; Mukaka, M; Taylor, WR (BioMed Central, 2024)
Background: With only one 15 mg primaquine tablet registered by a stringent regulatory authority and marketed, more quality-assured primaquine is needed to meet the demands of malaria elimination. Methods: A classic, two sequence, crossover study, with a 10-day wash out period, of 15 mg of IPCA-produced test primaquine tablets and 15 mg of Sanofi reference primaquine tablets was conducted. Healthy volunteers, aged 18–45 years, without glucose-6-phosphate dehydrogenase deficiency, a baseline haemoglobin ≥ 11 g/dL, creatinine clearance ≥ 70 mL/min/1.73 ms, and body mass index of 18.5–30 kg/m2 were randomized to either test or reference primaquine, administered on an empty stomach with 240 mL of water. Plasma primaquine and carboxyprimaquine concentrations were measured at baseline, then 0.25, 0.5, 0.75, 1.0, 1.25, 1.5, 1.75, 2.0, 2.333, 2.667, 3.0, 3.5, 4.0, 4.5, 5.0, 5.5, 6.0, 8.0, 10.0, 12.0, 16.0, 24.0, 36.0, 48.0 and 72.0 h by liquid chromatography coupled to tandem mass spectrometry. Primaquine pharmacokinetic profiles were evaluated by non-compartmental analysis and bioequivalence concluded if the 90% confidence intervals (CI) of geometric mean (GM) ratios of test vs. reference formulation for the peak concentrations (Cmax) and area under the drug concentration–time (AUC0–t) were within 80.00 to 125.00%. Results: 47 of 50 volunteers, median age 33 years, completed both dosing rounds and were included in the bioequivalence analysis. For primaquine, GM Cmax values for test and reference formulations were 62.12 vs. 59.63 ng/mL, resulting in a GM ratio (90% CI) of 104.17% (96.92–111.96%); the corresponding GM AUC0–t values were 596.56 vs. 564.09 ngxh/mL, for a GM ratio of 105.76% (99.76–112.08%). Intra-subject coefficient of variation was 20.99% for Cmax and 16.83% for AUC0–t. Median clearances and volumes of distribution were similar between the test and reference products: 24.6 vs. 25.2 L/h, 189.4 vs. 191.0 L, whilst the median half-lives were the same, 5.2 h. Conclusion: IPCA primaquine was bioequivalent to the Sanofi primaquine. This opens the door to prequalification, registration in malaria endemic countries, and programmatic use for malaria elimination. Trial registration The trial registration reference is ISRCTN 54640699